2023
DOI: 10.1002/chem.202300446
|View full text |Cite
|
Sign up to set email alerts
|

Quest of Quadruple Bonding Between Two Main‐Group Atoms in AeB and AeC (Ae=Ca, Sr, Ba) and the Role of d Orbitals of Heavier Alkaline‐Earth Atoms in Covalent Interactions

Abstract: Quantum chemical calculations using ab initio methods at the MRCI+Q(6,8)/def2‐QZVPP and CCSD(T)/def2‐QZVPP levels as well as density functional theory are reported for the diatomic molecules AeB− and isoelectronic AeC (Ae=Ca, Sr, Ba). The boride anions AeB− have an electronic triplet (3Σ−) ground state. The quintet (5Σ−) state is 5.8–12.3 kcal/mol higher in energy and the singlet (1Δ) state is 13.1–15.3 kcal/mol above the triplet. The isoelectronic AeC molecules are also predicted to have a low‐lying triplet (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 113 publications
(206 reference statements)
0
4
0
Order By: Relevance
“…30 The finding lead to a theoretical study of the diatomic anions AeB − and the isoelectronic neutral species AeC (Ae = Ca, Sr, Ba), which have an electron triplet ( 3 Σ − ) ground state. 31 The analysis of the bonding situation has shown that the six valence electrons occupy two bonding σ-orbitals with two electrons each and a degenerate π-orbital, in which each component has one electron. Accordingly, there are four occupied bond orbitals, but since there are only six valence electrons, the formal bond order is only three.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 The finding lead to a theoretical study of the diatomic anions AeB − and the isoelectronic neutral species AeC (Ae = Ca, Sr, Ba), which have an electron triplet ( 3 Σ − ) ground state. 31 The analysis of the bonding situation has shown that the six valence electrons occupy two bonding σ-orbitals with two electrons each and a degenerate π-orbital, in which each component has one electron. Accordingly, there are four occupied bond orbitals, but since there are only six valence electrons, the formal bond order is only three.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, there are four occupied bond orbitals, but since there are only six valence electrons, the formal bond order is only three. 31 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, weaker bond interactions are understood by longer bonds. 49,50 Notably, many properties are determined by the bond length, such as the biological activity, polarity, phase of matter, and reactivity. 51 Graphene has a monolayer (single layer) of carbon atoms tightly bonded in a hexagonal honeycomb, and AlN wurzite has a thermodynamically stable crystal structure.…”
Section: Geometry Optimizationmentioning
confidence: 99%